Behavior Trend of Buying Mask as A New Lifestyle for Women in The City of Surabaya During Pandemic - Febriandita Tedjomurti; Bagong Suyanto (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
The spread of the COVID-19 in Indonesia has changed various aspects of the life of the Indonesian people. The lifestyle of the people in the city of Surabaya which is advanced and modern makes the community, especially women, pay attention to their appearances. This causes the trend of masks circulating in society today to become increasingly diverse following the wishes of consumers. This research wants to see how the phenomenon of buying masks by women in Surabaya has become part of the lifestyle during the pandemic. The method used was data collection techniques carried out in two stages, primary namely questionnaires and in-depth interviews as a complement to secondary information, namely with data from various sources such as journals, books, web, and other data center agencies. The respondents interviewed were selected purposively with predetermined criteria. After all, data is processed, the data findings are interpreted and analyzed using the consumerism theory of Jean Baudrillard. This research resulted in the conclusion that most women in the city of Surabaya bought this type of cloth mask. Women in the city of Surabaya consider that masks not only have a health function as the main factor but also must have a fashion function.